The quality and reliability of the mechanical stethoscopes and Laser Doppler Vibrometer (LDV) to record tracheal sounds. (April 2020) - Aygün, Haydar; Apolskis, Aleksejs
Abstract: The sound of breathing activity can be used to assess the state of the lungs and detect adverse problems involving respiratory failure. Traditionally, mechanical stethoscopes are used for respiratory auscultation to analyse the lung sounds. Firstly, measurements are carried out on the five different standard stethoscopes to assess their reliability for detecting respiratory sounds in people. Secondly, three human subjects were used for tracheal sound experiments using the five stethoscopes. Thirdly, a Laser Doppler Vibrometer was used to detect tracheal sounds from three human subjects. The five stethoscopes used for measurements give different results, especially above 150 Hz. Experimental results show that mechanical stethoscopes are not reliable tools for assessing lungs sounds in people.